Lytic and mechanical stability of clots composed of fibrin and blood vessel wall components. Issue 3 (13th March 2013) - Rottenberger, Z.; Komorowicz, E.; Szabó, L.; Bóta, A.; Varga, Z.; Machovich, R.; Longstaff, C.; Kolev, K.
Summary Background Proteases expressed in atherosclerotic plaque lesions generate collagen fragments, release glycosaminoglycans (chondroitin sulfate [CS] and dermatan sulfate [DS]) and expose extracellular matrix (ECM) proteins (e.g. decorin) at sites of fibrin formation. Objective Here we address the effect of these vessel wall components on the lysis of fibrin by the tissue plasminogen activator (tPA)/plasminogen system and on the mechanical stability of clots. Methods and results MMP‐8‐digested collagen fragments, isolated CS, DS, glycosylated decorin and its core protein were used to prepare mixed matrices with fibrin (additives present at a 50‐fold lower mass concentration than fibrinogen). Scanning electron microscopy (SEM) showed that the presence of ECM components resulted in a coarse fibrin structure, most pronounced for glycosylated decorin causing an increase in the median fiber diameter from 85 to 187 nm. Rheological measurements indicated that these structural alterations were coupled to decreased shear resistance (1.8‐fold lower shear stress needed for gel/fluid transition of the clots containing glycosylated decorin) and rigidity (reduction of the storage modulus from 54.3 to 33.2 Pa). The lytic susceptibility of the modified fibrin structures was increased. The time to 50% lysis by plasmin was reduced approximately 2‐fold for all investigated ECM components (apart from the core protein of decorin which produced a moderate reduction of the lysis time by 25%), whereas fibrin‐dependent plasminogen activation by tPA was inhibited by up to 30%. Conclusion ECM components compromise the chemical and mechanical stability of fibrin as a result of changes in its ultrastructure.